2014
DOI: 10.1128/ec.00332-13
|View full text |Cite
|
Sign up to set email alerts
|

Small-GTPase-Associated Signaling by the Guanine Nucleotide Exchange Factors CpDock180 and CpCdc24, the GTPase Effector CpSte20, and the Scaffold Protein CpBem1 in Claviceps purpurea

Abstract: bMonomeric GTPases of the Rho subfamily are important mediators of polar growth and NADPH (Nox) signaling in a variety of organisms. These pathways influence the ability of Claviceps purpurea to infect host plants. GTPase regulators contribute to the nucleotide loading cycle that is essential for proper functionality of the GTPases. Scaffold proteins gather GTPase complexes to facilitate proper function. The guanine nucleotide exchange factors (GEFs) CpCdc24 and CpDock180 activate GTPase signaling by triggerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 89 publications
(133 reference statements)
1
16
0
Order By: Relevance
“…Those processes were shown to be regulated by the Nox‐complex in fungi (Brun et al ., ; Takemoto et al ., ; Kayano et al ., ; Ryder et al ., ). Moreover, Δ bciqg1 match the phenotype of mutants of other Nox complex components like BcRac, BcCdc42 and BcBem1 partially in B. cinerea as well as in other fungi (Takemoto et al ., ; Herrmann et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Those processes were shown to be regulated by the Nox‐complex in fungi (Brun et al ., ; Takemoto et al ., ; Kayano et al ., ; Ryder et al ., ). Moreover, Δ bciqg1 match the phenotype of mutants of other Nox complex components like BcRac, BcCdc42 and BcBem1 partially in B. cinerea as well as in other fungi (Takemoto et al ., ; Herrmann et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…during CAT formation, for BcNoxB during appressorial penetration). Additional subunits, like Bem1, which possesses similar protein domains as the mammalian p40phox, or the GEF (guanine nucleotide exchange factor) Cdc24 have been identified in fungi and were shown to interact with NoxR in E. festucae and C. purpurea (Takemoto et al ., ; Schürmann et al ., ; Herrmann et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…It was shown that the scaffold protein Bem1, whose domain structure is similar to that of p40phox, interacts with NoxR in Epichloë festucae and C. purpurea via their PB1 domains (Takemoto et al ., ; Schürmann et al ., ). Furthermore, the guanine nucleotide exchange factor Cdc24 also interacts with NoxR in E. festucae and C. purpurea (Takemoto et al ., ; Herrmann et al ., ). Recently, the tetraspanin Pls1, also a transmembrane protein, was suggested to be associated with NoxB.…”
Section: Introductionmentioning
confidence: 97%
“…E. festucae , suggest that the scaffold protein Bem1 and the GEF (guanine nucleotide exchange factor) Cdc24 are part of the Nox complex. In E. festucae and C. purpurea a direct interaction via the PB1 domains (Phox and Bem1p -mediates protein-protein interactions) was shown between NoxR, Bem1 and Cdc24 (Herrmann et al 2014 ;Schürmann et al 2013 ;Takemoto et al 2011 ). Comparable studies in B. cinerea did not show a similar interaction of Bem1 and Cdc24 with NoxR.…”
Section: Components Of B Cinerea Nox Complexes Function and Organizmentioning
confidence: 78%